BILINGUAL EDUCATION AS A MEANS OF LEARNING FOREIGN LANGUAGES IN UKRAINE AND EU - Ніна Нікольська (National Academy of Educational Sciences of Ukraine, 2021)
The main tasks were determined: the study of bilingual education phenomenon involved a theoretical analysis of the pedagogical domestic experience; it was carred out the essential characteristics of the basic concepts in the context of the problem under study. In the article the author considers the content of the terms "bilingual education" and "bilingual instruction". The author claims that these two concepts are often used in pedagogical sources. The analysis of these two directions and their main features is carried out, the author considers it necessary to distinguish between these two concepts: the cultures from which these two languages originated. Bilingual instruction is a process by which curricula or approaches are designed to facilitate learning for non-English-speaking students in primary and secondary schools by teaching them in their native language and in English. The author concludes that the bilingual education is a means of obtaining education using two languages as a means of teaching, in the process of which a personality is formed, open to interact with the outside world.